(untitled) (Cadernos de Letras da UFF, 2021)
The main goal of this article is to give a general overview on the standardization process of the French language in Louisiana. After examining the sociolinguistic situation of Louisiana French and discussing the notion of “standard language”, following the definitions of Bagno (2011) and Milroy & Milroy (1999), we will try to understand what recovers the notion of “Standard French”. Thereafter, we will analyze how its introduction in Louisiana has triggered some issues on the linguistic norm to be used during the revitalization movement, which began in the 1960s, and how these debates influenced the French norm used nowadays in Louisiana.